An Empirical Analysis Macroeconomics On Islamic Mutual Funds In Indonesia - Mauizhotul Hasanah; Muhammad Ubaidillah Al-Mustofa; Sri Herianingrum (JURNAL MANAJEMEN DAN BISNIS INDONESIA, 2020)
Macroeconomic factors are indicators to be considered by fund managers and investors before allocating funds for investment. The study aims to discover a causal relationship and test for long-term relationship between macroeconomic variables consisting of inflation, interest rate and currency exchange rate against Islamic mutual funds. The research used secondary monthly data related to macroeconomic variables and Islamic mutual funds during 2011-2016. This study uses a quantitative approach with a model of Vector Auto Regression (VAR). The empirical results show that there are no long-term relationship between the variables of inflation, interest rates, and exchange rate against Islamic mutual fund. Granger causality test shows that the three variables of inflation, interest rates, and exchange rates has no causal relationship, but there are two one-way relationships, which include the interest rate and Islamic mutual funds, and Islamic mutual funds and the exchange rate.